Synthesis and Characterization of the First 2 D Neptunyl Structure Stabilized by Side‐on Cation–Cation Interactions. Issue 9 (30th January 2013) - Vlaisavljevich, Bess; Miró, Pere; Ma, Dongxia; Sigmon, Ginger E.; Burns, Peter C.; Cramer, Christopher J.; Gagliardi, Laura
<x xml:space="preserve">Abstract</x> Cation–cation interaction: A new 2 D sheet structure containing a side‐on cation–cation interaction (CCI) has been synthesized and characterized (see figure). Unprecedentedly, no chelating ligands between the cations are present. The nature of the side‐on interaction and ligand effects has been explored by using a variety of quantum chemical methods. The spin–orbit‐coupled ground state mixes singlet, triplet, and quintet‐pure spin states.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>